PERSEPSI DAN PREFERENSI KONSUMEN INDONESIA TERHADAP PRODUK ASING DAN PRODUK LOKAL MELALUI MEDIA SOSIAL - Ruth Nehemia Staal; Marina Wardaya (Jurnal Vicidi, 2021)
This literature review was conducted with the aim of collecting supporting data of perception and preference of Indonesian consumers towards foreign and local product, about ethnocentrism as well as the role of social media in shaping consumer perception and preference. The method used is literature study by collecting the results of pre-existing studies to answer the problems. The studies are sourced from international journals and national journals to support the level of accuracy of this journal. The result of the study shows that there is difference in consumer perception and preference of foreign and local product, so it is necessary to improve the quality of local product that it would be possible to compete with foreign product. Keywords: Consumer’s Perception, Consumer’s Preference, Local Product, Foreign Product, Social Media